HUBUNGAN KECEMASAN DENGAN KUALITAS HIDUP ORANG DENGAN HIV/AIDS - Sondang Ratnauli Sianturi; Sri Winda Rizky (Jurnal Keperawatan Malang, 2021)
Background: In people with HIV / AIDS, infection from the virus becomes part of a chronic disease that causes high psychological stress. Anxiety itself is needed to survive, but in people with HIV / AIDS, who has higher anxiety level than the average person, it can reduce the quality of life . Purpose: This study aimed to find the relation between anxiety and the quality of life of people with HIV / AIDS at the Pelita Ilmu Foundation in Tebet, South Jakarta. Method: This study used quantitative descriptive design. The sampling method used was krejcie table, in which there were 145 samples obtained. Research tools used for measuring were the Hamilton Rating Scale for Anxiety (HRS-A) questionnaire, 1959 with a Cronbach Alpha of 0.756 and for the quality of life variable using the WHOQOL-HIV BREF questionnaire with a Cronbach Alpha value of 0.513-0.789. Results: The results showed that there were as many as 90 respondents who experienced anxiety (62.1%) and there were 45 respondents (37.9%) who did not experience anxiety. Meanwhile, 102 respondents had high quality of life (70.3%) and 43 respondents (29.7%) had low quality of life. The result of the Kendall's tau-b statistics showed p-value of 0.797, which is more than 0.05 which indicates there is no relation between anxiety and quality of life. Recommendation: Health Workers need to carry out health promotion and assistance to people with HIV/AIDS who experience anxiety and identify other factors that cause anxiety, so that the quality of life can improve.